2022
DOI: 10.1158/1078-0432.ccr-21-2563
|View full text |Cite
|
Sign up to set email alerts
|

Translocon-associated Protein Subunit SSR3 Determines and Predicts Susceptibility to Paclitaxel in Breast Cancer and Glioblastoma

Abstract: Purpose: Paclitaxel (PTX) is one the most potent and commonly used chemotherapies for breast and pancreatic cancer. Several ongoing clinical trials are investigating means of enhancing delivery of PTX across the blood-brain barrier for glioblastomas (GBMs). Despite the widespread use of PTX for breast cancer, and the initiative to repurpose this drug for gliomas, there are no predictive biomarkers to inform which patients will likely benefit from this therapy. Experimental Design: To identify predictive biomar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…PTX is a commonly used chemotherapy drug for a variety of cancers and interferes with cell mitosis mechanism. As a first‐line chemotherapy drug for breast cancer, it has been extensively used to treat breast cancer, especially advanced metastatic breast cancer [47–49]. In our study, we observed that tumor sO 2 first increased and then significantly decreased after PTX treatment, which may be attributed to the anti‐angiogenic effects of PTX and its potential to improve the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 53%
“…PTX is a commonly used chemotherapy drug for a variety of cancers and interferes with cell mitosis mechanism. As a first‐line chemotherapy drug for breast cancer, it has been extensively used to treat breast cancer, especially advanced metastatic breast cancer [47–49]. In our study, we observed that tumor sO 2 first increased and then significantly decreased after PTX treatment, which may be attributed to the anti‐angiogenic effects of PTX and its potential to improve the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 53%
“…Paclitaxel (PTX) is a widely used and highly potent chemotherapeutic agent, being the basis of regimens to treat breast, pancreatic, ovarian, and lung non-small cell lung carcinomas [ 1 ]. However, it is estimated that half of the patients treated with PTX do not receive a therapeutic benefit, yet are exposed to its toxic effects, causing physical, psychological, and social discomfort [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In glioblastoma (GBM) treatment, PTX has proven a high efficacy at nanomolar concentrations in achieving in vitro tumor cell death, with an IC50 1,400-fold lower than temozolomide, standard-of-care treatment [ 2 4 ]. However, minimal response to PTX in patients was demonstrated in several clinical trials [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations